2019
DOI: 10.1038/s41598-019-56151-1
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effects of Anti-RANKL Antibody and Zoledronic Acid on Growth and Tooth Eruption in Growing Mice

Abstract: The anti-bone resorptive drugs denosumab, an anti-human-RANKL antibody, and zoledronic acid (ZOL), a nitrogen-containing bisphosphonate, have recently been applied for treatment of pediatric patients with bone diseases, though details regarding their effects in growing children have yet to be fully elucidated. In the present study, we administered these anti-resorptive drugs to mice from the age of 1 week and continued once-weekly injections for a total of 7 times. Mice that received the anti-RANKL antibody di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 55 publications
(75 reference statements)
1
13
0
Order By: Relevance
“…In contrast, bisphosphonate‐treated mice display delayed tooth root formation and tooth eruption with a significant reduction in the interradicular septum length. These mice exhibit increased osteoclasts and a significant reduction in osteoblast numbers in the alveolar bone 85 . These data suggest that both bone resorption and bone formation are critical for tooth eruption as well as root formation.…”
Section: Osteoclasts In the Jawbonementioning
confidence: 75%
See 4 more Smart Citations
“…In contrast, bisphosphonate‐treated mice display delayed tooth root formation and tooth eruption with a significant reduction in the interradicular septum length. These mice exhibit increased osteoclasts and a significant reduction in osteoblast numbers in the alveolar bone 85 . These data suggest that both bone resorption and bone formation are critical for tooth eruption as well as root formation.…”
Section: Osteoclasts In the Jawbonementioning
confidence: 75%
“…These mice exhibit increased osteoclasts and a significant reduction in osteoblast numbers in the alveolar bone. 85 These data suggest that both bone resorption and bone formation are critical for tooth eruption as well as root formation. 93,94 Clinical studies showed that administration of PGE2 accelerates orthodontic tooth movement without any obvious side effects.…”
Section: Osteoclast Function In Tooth Eruptionmentioning
confidence: 94%
See 3 more Smart Citations